Production, use and trade of gaharu in Peninsular Malaysia - Lim, Hin Fui; Mamat, Mohd Parid; Chang, Yu Shyum (2007)
Gaharu, known as agarwood, aloeswood, eaglewood, oudh (Arabic), chen-xiang (Chinese) and jinkoh (Japanese), is the resin-impregnated deposits formed in some trees of the family Thymelaeaceae. The fragrant gaharu products are used by Muslims, Christians, Buddhists and Hindus. They are highly demanded in international market. The best grade of gaharu wood is sold as high as RM16,000 in Kuala Lumpur in October 2007. On the production side, there are about 4,100 gaharu harvesters in Peninsular Malaysia in 2007. Local harvesters, comprising Orang Asli, Malay and Thai descendants, practise responsible harvesting. However, since 1980s, with the encroachment of foreign harvesters (especially the Thai), the resources are depleting in our natural forests. Gaharu wood produced is sold to local traders. These local traders then sell the high grade gaharu to other middlemen or export them to Singapore and Middle East. The low grade wood is processed into oil in Kelantan and Terengganu before it is marketed. In some cases, the Arab traders come personally to purchase the wood and oil directly from the local middlemen. There is practically little use of gaharu by the Malaysian population. Processed oil of 12-ml is packed in small bottle and sold at about RM300, which is regarded expensive by many Malaysians. The use of gaharu products lies in the international market. While production of gaharu provides income to local harvesters and traders, it may not be a long term source of income as resources are depleting. There is international demand for gaharu products. It is recommended that the planting of gaharu-producing trees and the processing of gaharu products be encouraged and supported by government research and development. The industry is a potential income-generating activity for the country.